2019
DOI: 10.1002/clc.23187
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in asymptomatic stage B heart failure with Type II diabetic mellitus

Abstract: Background The presence of concomitant Type II diabetic mellitus (T2DM) and depressive symptoms adversely affects individuals with symptomatic heart failure (HF). Hypothesis In presymptomatic stage B HF, this study hypothesized the presence of greater inflammation and depressive symptoms in T2DM as compared to non‐T2DM Stage B patients. Methods This cross‐sectional study examined clinical parameters, inflammatory biomarkers, and depressive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Individuals with HF have consistently elevated depressed mood and anxiety [21,60], which correlates with significantly poorer clinical outcomes, including morbidity and mortality [61,62]. It may be therefore that for individuals with asymptomatic HF, engaging in spiritual practices (as mindfulness has been recently proposed [63], could help support and improve their clinical symptoms and psychosocial well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with HF have consistently elevated depressed mood and anxiety [21,60], which correlates with significantly poorer clinical outcomes, including morbidity and mortality [61,62]. It may be therefore that for individuals with asymptomatic HF, engaging in spiritual practices (as mindfulness has been recently proposed [63], could help support and improve their clinical symptoms and psychosocial well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from the cardiology clinics at University of California San Diego (UCSD) and at the Veterans Affairs San Diego Healthcare System (VASDHS) between 2011-2014. The presence of Stage B HF was defined as structural heart disease based on recommendations and cut-points from the American Society of Echocardiography guidelines [20,21].…”
Section: Samplementioning
confidence: 99%
“…Kikuchi and colleagues established an animal model, and found that sST2 overexpression may reduce social behavior and enhance depressive‐like behavior by changing the composition of gut microbiota [34]. Another study conducted in 349 type 2 diabetes mellitus (T2DM) and non‐T2DM men with asymptomatic stage B heart failure (HF) indicated that T2DM HF patients had higher circulating levels of sST2 and had more somatic/affective depressive symptoms [14]. Furthermore, a study including 233 consecutive HF patients demonstrated that sST2 was independently related to depression scores for the Hospital Anxiety and Depression Scale, and patients with both elevated sST2 and depression had a 4.9‐fold increased risk of all‐cause mortality and rehospitalization for HF [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sST2 has the role of enhancing phagocytosis, which could be an important response to vascular injury[12], and higher concentrations of sST2 were associated with incident stroke [13]. It is reported that sST2 is an independent predictor of somatic/affective depression [14]. However, there is sparse literature on the relationship between sST2 level and subsequent depression after ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation